Social policy review. edited by Catherine Bochel, Nick Ellison and Martin Powell. - Bochel, Catherine; Ellison, Nicholas, 1952-; Powell, Martin (The Policy Press, 2003)
Social Policy Review 15 continues the tradition of providing a different style and approach to policy issues from that found in most academic journals and books. This volume combines issues such as globalization, Europe and pensions with an examination of the current and historical contexts of social policy.